Characterization and Use of Folate Receptor Isoforms for Targeting of Epithelial and Myeloid Cells - (:unkn) unknown (My University, 2016)
ABSTRACT CHARACTERIZATION AND USE OF FOLATE RECEPTOR ISOFORMS FOR TARGETING OF EPITHELIAL AND MYELOID CELLS by Sreya Biswas The University of Wisconsin-Milwaukee, 2016 Under the Supervision of Professor Douglas A. Steeber Folate receptor (FR) is a GPI-anchored glycoprotein with high binding affinity for folic acid. FR has two membrane-associated isoforms, α and β, that are overexpressed on epithelial and myeloid tumors, respectively. Normal cells may also exhibit FR expression at very low levels but interestingly, FR-α on normal cells is restricted to the apical surface i.e., away from the blood stream. This differential expression and orientation of the FR-α isoform on tumor cells has been exploited to selectively target and deliver conjugates (e.g., drugs, nanoparticles, liposomes) to tumor cells without harming neighboring healthy cells. However, the functions and use of FR-β as a potential target have not been explored, and its functions on myeloid cells remain largely unknown. Therefore, we investigated the functions of FR-β to determine its potential as a target in myeloid malignancies using a human myelomonocytic leukemia cell line, U937. FR-α studies were conducted using a murine epithelial breast carcinoma cell line, 4T1, and tumors harvested from 4T1 tumor-bearing mice. The isoforms were found overexpressed on tumor cells and tissues, both in vitro and in vivo, with no expression observed on corresponding normal cells. Studies conducted using folic acid-fluorochrome conjugates to determine intracellular receptor fate indicated that FR-β was not internalized into cells unlike FR-α. However, both isoforms exhibited strong binding to folic acid conjugates (e.g., fluorochromes, nanoparticles) thus indicating that they could be selectively targeted using folic acid-dependent methods. We also determined the potential of a novel histone deacetylase (HDAC) inhibitor (HDACi) as an anti-cancer agent that could be used along with folic acid for achieving better selectivity in targeting tumor cells. Preliminary studies showed that Compound 5 (Cpd5) is stable with strong anti-proliferative activities against human tumor cells. Cpd5 was also able to reduce the rate of 4T1 tumor growth in mice without inducing systemic toxicity in the animals. In addition, Cpd5 exhibited desirable pharmacokinetic properties and showed direct effects on acetylation levels of histone proteins. These studies not only provide insights into the functional differences associated with FR-α and FR-β isoforms, but also highlight the potential of future targeting strategies utilizing these to target both epithelial and myeloid malignancies with improved selectivity.